1982
DOI: 10.1111/j.1532-5415.1982.tb01279.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Sleep and Waking EEGs of Nondemented and Demented Elderly Subjects

Abstract: Sleep and waking EEGs from 11 healthy nondemented elderly men and from ten inpatients for whom the diagnosis was probable senile dementia of Alzheimer's type (SDAT), were monitored in the subjects' typical home or ward environments or in the sleep laboratory, according to their customary sleep schedules. Aged normal subjects (age range, 56-85 years) had less Stage 3 and Stage 4 sleep, less REM sleep, and more wakefulness than normally observed in young adults. Patients with SDAT (age range, 56-88 years) had ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
155
1
3

Year Published

1984
1984
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(165 citation statements)
references
References 28 publications
6
155
1
3
Order By: Relevance
“…Sleep disturbances that have been reported in AD patients include significant loss of SWS and REM sleep, as well as increases in the latency to the first REM sleep episode and an increase in the amount of wakefulness and EEG slowing during wake and during REM sleep (2,32,41). Such perturbations in sleep structure lead to the breakdown of sleep/wake circadian rhythms and marked attenuations in delta sleep (31,41,48,61,62).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep disturbances that have been reported in AD patients include significant loss of SWS and REM sleep, as well as increases in the latency to the first REM sleep episode and an increase in the amount of wakefulness and EEG slowing during wake and during REM sleep (2,32,41). Such perturbations in sleep structure lead to the breakdown of sleep/wake circadian rhythms and marked attenuations in delta sleep (31,41,48,61,62).…”
Section: Discussionmentioning
confidence: 99%
“…Such perturbations in sleep structure lead to the breakdown of sleep/wake circadian rhythms and marked attenuations in delta sleep (31,41,48,61,62). The current experiments were conducted in younger mice, and as such, the magnitude of sleep alterations was not observed during baseline conditions but became apparent during the recovery period from any of the three experimental sleepdisrupting paradigms used herein.…”
Section: Discussionmentioning
confidence: 99%
“…For purposes of this study, scoring of nonrapid eye movement (NREM) sleep was modified to quantify the loss of stage 2 EEG sleep transients (spindles and K-complexes) previously noted by other investigators to be characteristic of some, although not all, elderly subjects (both normals and dementing) (7,21,22): Thus, \\le have designated a category of NREI\1 sleep as "indeterminate" if it has a stage 2 appearance except for the absence of spindles and K-complexes. "Indeterminate" NREM sleep (designated stage "N") is distinguished from stage 1 sleep by the absence of slow eye movements and by not being a transitional stage to or from wakefulness.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to changes in SWS and REM, electroencephalography (EEG) studies have shown specific changes to delta waves, sleep spindles and K complexes during sleep in the elderly. It has been hypothesized that some of these changes might be early biological markers of the gradual deterioration of the central nervous system with age [45].…”
Section: Sleep and The Elderlymentioning
confidence: 99%